Implementing a pressure training program to improve decision-making and execution of skill among premier league academy soccer players. Issue 4 (4th July 2022) - Kent, Sofie; Devonport, Tracey J.; Lane, Andrew M.; Nicholls, Wendy
Abstract: The present study evaluated the effectiveness of an intervention intended to improve academy players' performance under pressure. Male academy soccer players ( n  = 82; mean age = 14.12 years, SD  = 2.28) completed a baseline pressure task producing performance scores (A) for decision making and skill execution. By completing a pressure task, players received pressure training (PT) (Wood & Wilson, 2012). Players were then randomly allocated to an intervention group ( n =  41; receiving PT, three cognitive behavior workshops, and reflective diaries) or comparison group ( n =  41; receiving PT only). Sixty-eight players ( n  = 29; intervention group; n  = 39; comparison group) repeated the PT task at a six-week follow up (B), and of these, 26 ( n  = 15; intervention group; n  = 11; PT only) also completed a re-test PT task (A) at 12-week follow up. Due to attrition at follow up, chi-square analysis was conducted across experimental groups A-B only. Analysis indicated intervention players scored significantly higher in their decision-making ( p = .028) with a significant main effect of age-group on decision-making ( p = . 003) and skill execution ( p = .005). Four players (highest scoring and lowest scoring player within intervention and comparison groups) from each academy age-group ( n =  16) took part in individual interviews to explore intervention effectiveness. Thematic analysis found that some players perceived no benefits of the condition they completed, others perceived benefits to confidence, meta-cognitive skills, and challenge appraisals. Methodological implications for future pressure training interventions are presented. Lay summary : This study offers partial support in the effectiveness of contextualized pressure program to enhance elite academy players' ability to cope with performance pressure. Some players felt the intervention had no benefits, whilst others said there were benefits for confidence, ability to understand helpful emotions and thoughts when performing under pressure. Implications for Practice: A contextualized pressure intervention comprising of pressure training, cognitive behavioral workshops and reflective diaries can facilitate performance under pressure by enhancing coping skills. Organizational support and endorsements from key personnel (e.g., academy manager, coaches, and senior coaches) for all components of pressure interventions is important in supporting player engagement. To optimize pressure training, practitioners should focus on how to incorporate pertinent situational and personal incentives within pressure training.